The effect of efficiency ratio, Bad Credit and Profitability to Capital Adequacy Ratio at Sharia Commercial Banks in Indonesia Year 2014-2018 - Tyas, Sulistyaning; Wuryani, Eni (Ekspektra : Jurnal Bisnis dan Manajemen, 2021)
This study aims to determine the effect of efficiency ratios, non-perfoming loans, and profitability on the capital adequacy ratio in Islamic Commercial Banks in Indonesia 2014-2018. This research is a quantitative study with secondary data from financial reports. Purposive sampling is a sampling technique use in this study so that there are 14 samples of Islamic commercial banks during the 2014-2018 period. The data analysis used is multiple linear regression analysis with the SPSS application. The results obtained by two dependent variables, the efficiency ratio and non-performing loans have an influence on the capital adequacy ratio. Meanwhile, profitability partially has no effect on the capital adequacy ratio.